Identifying mental illness and monitoring mental health in probation service settings - Brooker, Charlie (European journal of probation, 2022)
There is a need to improve a) identification and monitoring of people with mental illness on probation and b) understanding of the impact of interventions on mental health outcomes for the probation population. If data were routinely collected using validated screening tools and shared between agencies, this could inform practice and commissioning decisions, and ultimately it could improve health outcomes for people under supervision. The literature was reviewed to identify brief screening tools and outcome measures that have been used in prevalence and outcome studies conducted with adults on probation in Europe. This paper shares findings from the UK-based studies in which 20 brief screening tools and measures were identified. Recommendations are made based on this literature regarding suitable tools for use in probation to routinely identify a need for contact with mental health and/or substance misuse services and to measure change in mental health outcomes.